KONTRIBUSI MUTU INFORMASI TERHADAP EFEKTIVITAS KERJA PEGAWAI BIDANG PENDIDIKAN MENENGAH DAN TINGGI DI DINAS PENDIDIKAN PROVINSI JAWA BARAT (Jurnal Tata Kelola Pendidikan, 2019)
The tittle of this research is "Contribution of Information Quality of WorkEffectiveness Against Employee Education and Higher Secondary EducationDepartment of West Java Province". In general, this study aims to determine howmuch influence the quality of information on the effectiveness of employees working inthe field Dikmenti Education Department of West Java Province. The method used inthis research is descriptive method with quantitative approach. The data collectiontechnique using a closed questionnaire distributed to 49 employees as the studypopulation (total sampling). Weight calculation results Mean Score (WMS), shows thatthe quality of information included in either category with a score of 2.97 and theeffectiveness of the employees included in the excellent category with a score of 3.08.Normality test results on the distribution of the data showed that the variables X and Yhave normal distribution, further analysis of the data using statistical parametric. Thecorrelation analysis using Pearson Product Moment correlation coefficient betweenvariables X and Y is equal to 0.742 which shows that the correlation of the twovariables are at the level of positive relationships and strong. Meanwhile, the resultsof significance test using t-test comparison is t_hitung (7.579)> t_tabel (2,012) meansthat there is a significant relationship between the variables X and Y. Further, testresults of the coefficient of determination is that the variable X contributes to variableY for 55% and the rest 45% influenced by other factors. Results of regression analysisequation Y = 13.955 + 0.742 X. The conclusion is evident that there is a strong andsignificant relationship between Quality of Work Effectiveness Against InformationOfficer of Secondary and Higher Education in the Education Department of West JavaProvince.
Keywords: Quality of Information; Effectiveness Work.